Dielectric, Ultrasonic and Viscoelastic Properties of Rubber Wood - Kabir, Md. Firoz (1998)
Dielectric, ultrasonic and viscoelastic properties of rubber wood were studied with various physical parameters, such as moisture contents (MC), grain directions and temperatures. Three anisotropic directions, namely longitudinal, radial and tangential to the growth ring were considered for the measurement of these properties. Dielectric properties were measured at low frequencies from 10⁻² to 10⁻⁵ Hz and at microwave frequencies from 1 to 18 GHz. Ultrasonic properties were determined with a commercial ultrasonic tester at 45 kHz. Viscoelastic properties were carried out with the Dynamic Mechanical Thermal Analyzer at frequency ranging ,from 0.01 to 1 00 Hz. At low frequencies, five types of dielectric mechanism were observed for different MC such as 1) less than 5%, 2) 5-10%, 3) 11 - 17%, 4) 18-25% and 5) more than 25%. Dielectric constant increased with temperature for these frequencies while dielectric loss factor showed minimum value in oven-dry condition. Dielectric constant and dielectric loss factor varied in the order of longitudinal> radial 2:. tangential directions. Dielectric data at low frequency are in well agreement with those calculated from equivalent circuit using the concept of universal capacitor. Three equivalent circuits fitted well for data at very low MC or for oven-dried wood, MC below fiber saturation point and MC above fiber saturation point. Activation energies were 0.27eV, 0.34eV and 0.41eV for longitudinal, radial and tangential directions respectively. At microwave frequencies, dielectric constant and dielectric loss factor were found to increase with MC ranging from oven-dry up to saturation point. Dielectric constant also decreased with temperature and dielectric loss factor exhibited peaks at 10 GHz. Dielectric constants are predicted well by Winner, Lichteneker and generalized equations with lower value of the exponents. Above 3 G Hz, dielectric loss factor fitted well with the predicted values using Winner, Kraszewski, Looyenga or with generalized equations with lower values of the exponents. Below 3 GHz, dielectric loss factor are unpredictable by these mixture equations.